ANALISIS KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN LQ 45 GO PUBLIC DI BURSA EFEK INDONESIA - Hari Gursida (MAGMA : JURNAL MAGISTER MANAJEMEN, 2013)
The purpose of this study is to analyze the financial performance of the company's stock return at LQ 45 go public in Indonesia Stock Exchange. Thecompany's financial performance is measured by using the Net Profit Margin(NPM), Total Assets Turnover (TATO), and Debt to Equity Ratio (DER). The population for this study is LQ 45 with a total sample of 20 companies.Collected data is processed using the technique of path analysis (path analysis). The results showed that the NPM has a direct positive influence on stockreturns with 41 path coefficient = 0.378 and 2.645 t NPM with significance ? of0.05, the significance of t ? Addressing NPM 37.8% effect on stock returns. Inthis study the effect on stock returns TATO has 41 beta coefficient = -0.001 witha significant level thitung TATO on stock return is -0.010 to 0.992 for ? so TATOhas no effect on stock returns. Based on the results of path coefficient analysis showed that DER directimpact negatively on the Stock Return with direct negative influence on 43path coefficient = -0.308. This means that if DER declining, stock returns willincrease.Keywords: Net Profit Margin (NPM), Total Assets Turnover (TATO), Debt to Equity Ratio (DER), and Stock Return